Instituiç\~oes, distribuiç\~ao de renda e crescimento econômico: Uma análise pós-keynesiana - Claudio Roberto Amitrano (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– The aim of this paper is to analyze the relationship between institutions, income distribution and growth in post-Keynesian tradition. Therefore, we developed a model that seeks to illustrate the way in which income distribution affects economic growth. Furthermore, we aim to show that the characterization of the economy as wage-led or profit-led is closely related to institutional settings of an economy and that has profound implications on the dynamics of growth.
Keywords: E12; O11; O43; 330; institutions; income distribution; economic growth